2022
DOI: 10.1021/acsomega.2c05265
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin-Supported Silver Nanoparticles as an Effective Catalyst for the Removal of Methylene Blue Dye from Aqueous Solutions

Abstract: Water contamination by organic dyes has become a reason for severe environmental pollution and has been threatening the aquatic ecosystem. In this study, kaolin-supported silver nanoparticle (Ag-NP) composites were synthesized by a facile two-step adsorption−reduction method through the reduction of silver ions adsorbed onto locally available, inexpensive, and easily pretreated kaolin surfaces by using sodium borohydride (NaBH 4 ) for the catalytic degradation of methylene blue (MB) dye in aqueous solution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…MB is a cationic thiazine (heterocyclic aromatic) dye having a wide range of applications in many industries and its massive amount is used in the textile industry . The oxidized form of MB has a deep blue aqueous solution, while the reduced form (leuco form) has a colorless solution . The optimum conditions recorded for the catalytic degradation of MB dye were 1.6 mL of 0.02 mM MB dye, 0.07 mL of 0.05 mg/mL solution of Ag–Cu BNP’s nanocatalyst followed by the addition of 0.5 mL of 2 mM NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MB is a cationic thiazine (heterocyclic aromatic) dye having a wide range of applications in many industries and its massive amount is used in the textile industry . The oxidized form of MB has a deep blue aqueous solution, while the reduced form (leuco form) has a colorless solution . The optimum conditions recorded for the catalytic degradation of MB dye were 1.6 mL of 0.02 mM MB dye, 0.07 mL of 0.05 mg/mL solution of Ag–Cu BNP’s nanocatalyst followed by the addition of 0.5 mL of 2 mM NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…62 The oxidized form of MB has a deep blue aqueous solution, while the reduced form (leuco form) has a colorless solution. 63 The optimum conditions recorded for the catalytic degradation of MB dye were 1.6 mL of 0.02 mM MB dye, 0.07 mL of 0.05 mg/mL solution of Ag−Cu BNP's nanocatalyst followed by the addition of 0.5 mL of 2 mM NaBH 4 . Figure 7b shows that after 2 min, the peak at 664.5 nm disappeared, indicating the degradation of MB dye up to 98.57%.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Water pollution caused by toxic chemicals, such as organic dyes, heavy metal ions, biomolecules, etc., directly affects millions of people and animals worldwide, particularly in developing countries. [1][2][3][4] These pollutants may be produced by industrial effluents and various anthropogenic activities. In this regard, numerous scientific attempts have been made to develop efficient and cost-effective methods to remove these hazardous contaminants from water.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the use of Ethiopian kaolin as an efficient support material for silver nanoparticles for the conversion of toxic MB dye to the less-toxic leuko-methylene blue byproduct using NaBH 4 as a reducing agent. 23,24 However, in this work, we introduced an oxidation-based degradation of MB dye to other less-toxic byproducts (CO 2 , H 2 O, and low-molecular-weight organics) using inexpensive and a less-toxic oxidizing agent NaOCl, and an extremely inexpensive precursor material (Ni(NO 3 ) 2 •6H 2 O). The clay that was used as a support for NiO NPs was imported to the laboratory, and its treatment was performed based on the method reported by Asmare et al 24 with slight modifications.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, in this work, we introduced an oxidation-based degradation of MB dye to other less-toxic byproducts (CO 2 , H 2 O, and low-molecular-weight organics) using inexpensive and a less-toxic oxidizing agent NaOCl, and an extremely inexpensive precursor material (Ni(NO 3 ) 2 •6H 2 O). The clay that was used as a support for NiO NPs was imported to the laboratory, and its treatment was performed based on the method reported by Asmare et al 24 with slight modifications. A certain amount of raw kaolin clay was ground with mortar and pestle and passed through a 200 mm sieve.…”
Section: Introductionmentioning
confidence: 99%